Critical analysis on steganography technique in text domain - Utama, Sunariya; Din, Roshidi; Mahmuddin, Massudi (2016)
This papers presents several steganography method on text domain based on the perspective of researchers effort in last decade.It has been analyzed the categories of method steganography in medium of text; text steganography and linguistic steganography.The following aim on this paper is identifying the typical these two methods in order to recognize the comparison technique used in previous study.Especially, the explication techniques of text steganography which consist of word-rule based and feature-based technique is critical concern in this paper.Finally, the advantage characteristic and drawback on these techniques in generally also presented in this paper.